NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIA Heart failure complicating myocardial infarction. Role of aldosterone - Rozentryt, Piotr; Nowak, Jolanta; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Heart failure is one of the most serious complications of myocardial infarction, either acutely or in the chronic phase. Recent basic and clinical studies underscore the important role of aldosterone in pathogenesis of post-infarct heart failure. The article provides an in-depth review of recent literature on this subject. The first part describes the most important aspects of regulation of aldosterone secre-tion and its biological action at the organ and tissue level. Subsequently, the contribution of aldosterone in structural and electrical re-modelling of the heart after infarction is discussed in detail. The final part of the review focuses on long-term consequences of aldoster-one for the structure and function of the arteries and its relation to atherosclerosis development and progression.